Board gender diversity and firms' social engagement in the Gulf Cooperation Council (GCC) countries - Jizi, Mohammad (2021)
Purpose The Gulf Cooperation Council (GCC) countries form a unique socioeconomic environment that makes the conclusions of the prior literature not likely to be applicable. GCC countries have huge oil reserves, yet they are aiming at reducing oil dependency through enhancing transparency, increasing foreign direct investments and reforming their governance structure. Their firms are mainly family owned and have low female representation in leadership positions. The study seeks to fill a literature gap by providing a business case supporting the call for gender diverse boards for better governance. Design/methodology/approach The study examines a sample of GCC-listed firms for the years 2009–2018. Three measures are used to proxy for firm social engagement, namely, CSR strategy score, environmental, social and governance (ESG) disclosure score and social pillar score. To ensure whether the presence of women on board or the number of women on board is influential on social engagements, the authors use the existence of women on board and the percentage of women on board variables. Data are collected using Thomson Reuters, and generalized least squares (GLS) panel data regression is used to estimate relationships. Findings The authors find that female representation on GCC corporate boards is increasing, yet in a slow path. The reported results support the role of women on boards in prompting firms' social agenda and enhancing the level of sustainability reporting. The results also show that female board representation supports the implementation of climate change policy, business ethics policy and health and safety policy. Originality/value The paper evidence the add value of women participation on GCC corporate boards in enhancing boards' functionality and governance. The empirical findings encourage firms and policymakers in the GCC countries to increase the share of females on corporate boards to improve firms' citizenship and facilitate attracting foreign investors.